INCLUSIVE EDUCATION OF CHILDREN AND YOUTH IN THE FIRST YEAR OF COVID-19 PANDEMIC: INTEGRATIVE REVIEW - Barreto Colichi, Rosana Maria [UNESP]; Molina Lima, Silvana Andrea [UNESP] (Univ Estadual Parana, Escola Musica & Belas Artes Parana, 2022)
In order to identify the knowledge produced on inclusive education and the COVID-19 pandemic, we carried out an integrative literature review, with 22 articles, from 23 databases such as OneFile, PubMed, Web of Science, Sage Journals and Medline, published from January 2020 to January 2021. The pandemic revealed challenges such as lack of internet access, use of technologies, adapting activities to students with disabilities and limited support for children and caregivers. Negative impacts of isolation and lack of school environment reflect on future psychological and social problems. Adaptations in education systems and the development of pedagogical responses must be urgent due to the impacts on the learning and health of children and their caregivers.
Keywords: Special education; COVID-19; Caregiver; Family